VIEWS ON FORMING DEFINITIONS OF ASPECTUAL MEANINGS IN ENGLISH DICTIONARIES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
In English lexicography, which is rapidly developing on online platforms, there is a tendency to bring sources into the form of a universal dictionary. A definition dictionary is formed by combining thesaurus, etymological and translation dictionaries into excellent educational resources. In such sources, it is very important to approach the interpretation of words based on certain standard principles. In this case, it is necessary to fully cover the meaning of lexemes, and to realize their grammatical and stylistic indicators. Definitions are mainly made in the form of logical description, synonymy or allusion. Priority is given to having lexemes belonging to the same grammatical category in the word definition. The form of definition should be chosen based on the meaning characteristics of each morphological category, lexical-semantic group. The article analyzes the interpretation of the verb semes such as action, state, as well as the meaning of "process".